The Prevalence of Drug Abuse as it Relates to Psychosocial Reasons among University Athletes in Selected Competitive Sports in Kenya - Ramara, Timothy; Munayi , Simon; Bailasha, Nicholas; Chumba, Janet (International Journal of Psychology, 2023)
Purpose: The main objective of this study was to explore the prevalence of drug abuse as it relates to psychosocial reasons that include peer pressure, social environment, emotional state and relationships; among university athletes involved in selected competitive sports. Methodology: The study used a mixed methods research design with an intention to capture and utilize both qualitative and quantitative data. The study sample comprised 300 respondents. Out of the 300 students, 173 (57.7%) were male and 127 (42.3%) were female players derived from six selected competitive sports at the universities in Kenya. The selected sports were badminton, tennis, basketball, volleyball, soccer and rugby. Stratified sampling followed by simple random sampling was used to select 10 universities proportionately (4 private and 6 public), the method was the most appropriate to capture universities with women rugby in addition to the five other selected sports. The study sought to investigate the prevalence of drug abuse due to factors such as psychosocial, medicinal and competition. SPSS computer version 20 was used to process data. The data was presented in form of tables. Findings: Data indicated clearly that athletes had abused drugs due to various psychosocial reasons. The prevalence per gender was close at 18% and 12.12% for males and females respectively. Peer pressure was regarded as a great contributor to drug abuse among the youth. Another psychosocial indicator is the emotional state of a particular individual. Students, just like other members of society, go through various challenging situations in life. The other indicator regarding drug abuse due to psychosocial factors is depression. Four (4, 40%) of the 10 dean of students interviewed said that students were victims of drug abuse due to depression. They alluded the depression cases mostly to relationship issues and financial challenges while the students are in session. The data was presented in form of Tables. Unique Contribution to Theory, Practice and Policy: Social Learning Theory, Stress-Coping Theory and Social Control Theory may be used to anchor future studies. It is recommended that university athletes be sensitized on proper use of sports to relieve stress and maintain emotional balance. Further, only qualified coaches and sports officers should be allowed to mentor and man sports in the universities. According to some heads of sports seven out of the ten (70%) and 4 of the 10 (40%) deans of students interviewed, some coaches may not report cases of drug abuse by athletes. This could be attributed to the fact that the coaches, who mostly are on casual basis, could fear experiencing bad blood with the players thereby threatening their jobs. Trained sports officers and coaches should accompany the university athletes always and act as worthy mentors to the young athletes.